Orbital Exenteration and Brachytherapy for the Treatment of Pediatric, Fusion-positive, Recurrent Rhabdomyosarcoma - Joseph Lopez, MD, MBA; Nancy Qin, BA; Robbie Woods, MD; Marjorie Golden, MFA, CDT; Harrison Spatz, DMD, MS; Jatin Shah, MD; Leonard H. Wexler, MD; Joseph Randazzo, DDS; Suzanne L. Wolden, MD; David H. Abramson, MD (Plastic and Reconstructive Surgery, Global Open, 2022)
SUMMARY. A 20-month-old boy presented with biopsy-proven recurrent alveolar rhabdomyosarcoma without metastasis. He was previously treated with multiagent chemotherapy and external beam irradiation showing a complete response. Upon relapse, he was treated with chemotherapy, orbital exenteration, and brachytherapy. Customized, intraoperative brachytherapy has potential to limit the sequelae associated with radiation adjuvant therapy.